Factors That Improve Chest Computed Tomography-Defined Sarcopenia Prognosis in Advanced Non-Small Cell Lung Cancer - Yang, Ming; Tan, Lingling; Xie, Lingling; Hu, Song; Liu, Dan; Wang, Jing; Li, Weimin (Frontiers in Oncology, 2021)
Background: Whether muscle strength and physical performance should be components of sarcopenia remains controversial. This study evaluated the skeletal muscle index derived from computed tomography images at the 12th thoracic vertebra level (T12 SMI), handgrip strength, performance status, and their combination for predicting overall survival in patients with advanced non-small cell lung cancer. Methods: Chest computed tomography, handgrip strength measurement, and bioelectrical impedance analysis were performed. Sarcopenia was defined based on the T12 SMI alone or the T12 SMI, handgrip, and/or physical performance (i.e. Asian Working Group for Sarcopenia [AWGS]-defined sarcopenia or severe sarcopenia). Results: Overall, 639 participants were included; 488 (76.4%) died. At baseline, 160 (25.0%), 141 (22.1%), and 42 (6.6%) patients had computed tomography-defined sarcopenia, AWGS-defined sarcopenia, and AWGS-defined severe sarcopenia, respectively. Chest computed tomography-defined sarcopenia (hazard ratio [HR], 2.00; 95% confidence interval [CI], 1.65-2.43), AWGS-defined sarcopenia (HR, 2.00; 95% CI, 1.59-2.49), and AWGS-defined severe sarcopenia (HR, 3.01; 95% CI, 2.21-4.09) were more strongly associated with poor prognosis than a performance status score ≥2 (HR, 1.37; 95% CI, 1.10-1.73).Conclusions: Adding handgrip strength and the performance status score to chest computed tomography-defined sarcopenia improved its prognostic ability. Oncological sarcopenia research should focus on muscle mass, strength, and function.